Philip II’s Quest. The Appointment of Governors-General during the Dutch Revolt (1559-1598) - V. Soen (BMGN: Low Countries Historical Review, 2011)
Philip II’s Quest: The Appointment of Governors-General during the Dutch Revolt (1559-1598) Recent historiographical studies have presented the Habsburg appointment of governors-general during the Dutch Revolt as the outcome of factional infighting at the Spanish Court. While this so-called ‘faction model’ has yielded new insights, it also raises a number of problems. Firstly, in the new model, the role of the dynasty is unduly relegated to the background – even though Philip II’s appointment decisions were mainly driven by dynastic considerations. Secondly, the power struggle at the Spanish Court was not only a conflict between court factions, but also between noble houses vying for prestige and trying to secure positions for their offspring. Thirdly, there is an excessive focus on the Spanish Court, while the feuds between noble houses in the Low Countries also played a role in the interim appointments made during the Revolt. Finally, Philip II always looked for the most suitable candidate in terms of administration and warfare during the Dutch Revolt, in accordance with the constraints of the composite Spanish monarchy. Only the combination of these four (frequently contradictory) motives reveals how Philip II’s appointment of governors can be seen as a quest for the right man or woman in the right place.